Porous cellulose structure and resin composition

A cellulose porous structure with specific surface area and porosity characteristics improves transparency and impact strength in resin compositions by ensuring uniform dispersion and increased contact area, addressing the limitations of existing cellulose structures in resin compositions.

JP2024178894APending Publication Date: 2024-12-25FUJIFILM BUSINESS INNOVATION CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024049635
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-13
Filing Date
2024-03-26
Publication Date
2024-12-25

AI Technical Summary

Technical Problem

Existing cellulose structures used in resin compositions face challenges in maintaining transparency and impact strength when kneaded with transparent resins, often leading to decreased transparency and limited impact resistance due to poor dispersibility and low contact area.

Method used

A cellulose porous structure with specific surface area between 1 m²/g and 150 m²/g, porosity between 10% and 50%, and average diameter of 50 μm or less, made from cellulose or cellulose derivatives, which allows for uniform dispersion and increased contact area when kneaded with transparent resins.

Benefits of technology

The cellulose porous structure enhances the transparency and impact strength of resin molded articles by preventing secondary aggregation and improving dispersibility, maintaining resin transparency while increasing impact resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178894000001
    Figure 2024178894000001
  • Figure 2024178894000002
    Figure 2024178894000002
  • Figure 2024178894000003
    Figure 2024178894000003
Patent Text Reader

Abstract

To provide a porous cellulose structure that yields a resin molded product with high transparency and impact strength.SOLUTION: A porous cellulose structure includes at least one of a cellulose and a cellulose derivative as a main component, in which a specific surface area is 1 m2 / g or more and 150 m2 / g or less, and a void ratio is 10% or more and 50% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cellulose porous structure and a resin composition. [Background technology]

[0002] Patent document 1 proposes a method for producing a porous cellulose medium, comprising the steps of preparing a fluid, homogeneous composition containing cellulose acetate, a basic compound, and a solvent containing water, and gelling the composition by a deacetylation reaction of the cellulose acetate.

[0003] Patent Document 2 proposes "particles containing cellulose acetate, the particles having an average particle diameter of 80 nm or more and 100 μm or less, a sphericity of 0.7 or more and 1.0 or less, a surface smoothness of 80% or more and 100% or less, and a surface contact angle with water of 100° or more, and a total acetyl substitution degree of the cellulose acetate of 0.7 or more and 2.9 or less."

[0004] Patent Document 3 proposes "a resin composition comprising a polymer component (A) containing polylactic acid (a1) and a biodegradable aliphatic polyester (a2) having a melting point of 50 to 250°C, the polylactic acid (a1) being contained in an amount of 90 to 50% by weight and the aliphatic polyester (a2) being contained in an amount of 10 to 50% by weight, based on the total weight of the polylactic acid (a1) and the aliphatic polyester (a2), and the polylactic acid-based resin composition containing 0.1 to 100 parts by weight of a biodegradable natural product (B) per 100 parts by weight of the polymer component (A)." [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2016 / 159334 [Patent Document 2] International Publication No. 2020 / 188698 [Patent Document 3] Japanese Patent Application Publication No. 11-241009 Summary of the Invention [Problem to be solved by the invention]

[0006] The object of the present invention is to provide a cellulose porous structure containing at least one of cellulose and a cellulose derivative as a main component, the structure having a specific surface area of ​​1 m 2 / g or less than 150m 2 The object of the present invention is to provide a cellulose porous structure which can provide a resin molded product having higher transparency and impact strength than when the porosity exceeds 10% or the porosity exceeds 50%. [Means for solving the problem]

[0007] Means for solving the above problems include the following aspects. <1> Contains at least one of cellulose and a cellulose derivative as a main component, Specific surface area is 1m 2 / g or more 150m 2 / g or less, A cellulose porous structure having a porosity of 10% or more and 50% or less. <2> When the cellulose porous structure is kneaded with a resin, the cellulose porous structure is present in the resin with an average diameter of 50 μm or less. <1> The cellulose porous structure according to claim 1. <3> The number average molecular weight of the cellulose and the cellulose derivative is 15,000 or more. <1> or <2> The cellulose porous structure according to claim 1. <4> The cellulose derivative is cellulose acetate. <1> ~ <3> 13. The cellulose porous structure according to claim 12. <5> Transparent resin, <1> ~ <4> The cellulose porous structure according to any one of the above items, A resin composition comprising a kneaded product containing the above. <6> The haze value of the molded article of the resin composition is 15% or less when the thickness is 2 mm. <5> The resin composition according to claim 1. <7> Charpy impact strength is 2.5kJ / m 2 That's all. <5> or <6> The resin composition according to claim 1. Effect of the Invention

[0008] <1> According to the present invention, a cellulose porous structure containing at least one of cellulose and a cellulose derivative as a main component has a specific surface area of ​​1 m 2 / g or less than 150m 2 / g or more, or a porosity of less than 10% or more than 50%, a resin molded article having high transparency and impact strength can be obtained.

[0009] <2> According to the present invention, there is provided a cellulose porous structure which, when kneaded with a resin, gives a resin molded product having higher transparency and impact strength than when the cellulose porous structure is present in the resin with an average diameter of more than 50 μm. <3> According to the present invention, there is provided a cellulose porous structure which can give a resin molded article having higher transparency and impact strength than when the number average molecular weight of cellulose and cellulose derivatives is less than 15,000. <4> According to the present invention, there is provided a cellulose porous structure which can give a resin molded article having high biodegradability, transparency and impact strength as compared with the case where the cellulose derivative is cellulose acetate propionate.

[0010] <5> , <6> or <7> According to the present invention, a cellulose porous structure containing at least one of cellulose and a cellulose derivative as a main component has a specific surface area of ​​1 m 2 / g or less than 150m 2 The resin composition provides a resin molded product having higher transparency and impact strength than when a cellulose porous structure having a viscosity of more than 100 μm / g or a porosity of less than 10% or more than 50% is used. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described as an example. The description and examples are merely illustrative of the embodiment, and are not intended to limit the scope of the present invention. In the present specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the present specification, the upper or lower limit of the numerical range may be replaced with a value shown in the examples.

[0012] Each component may contain multiple types of the corresponding substance. When referring to the amount of each component in a composition, if the composition contains multiple substances corresponding to each component, the amount refers to the total amount of those multiple substances present in the composition, unless otherwise specified.

[0013] <Cellulose porous structure> The cellulose porous structure according to this embodiment contains at least one of cellulose and a cellulose derivative as a main component, and has a specific surface area of ​​1 m 2 / g or more 150m 2 / g or less, and the porosity is 10% or more and 50% or less. The cellulose porous structure according to this embodiment is, for example, a powder containing at least one of cellulose and a cellulose derivative as a main component.

[0014] The cellulose porous structure according to this embodiment has the above-mentioned configuration, and thus a resin molded article having high transparency and impact strength can be obtained. The reason for this is presumed to be as follows.

[0015] Cellulose structures, which are mainly composed of cellulose and cellulose derivatives, are rapidly biodegradable in any environment, such as compost, activated sludge, or seawater, and are therefore in practical use for a variety of applications. One of its uses is as a modifier for improving impact strength.

[0016] However, when the cellulose structure is kneaded into the transparent resin, the transparency of the resulting resin composition (i.e., the resin molded product obtained from the resin composition) may decrease. This is believed to be due to the low dispersibility of the cellulose structure, which is difficult to finely disperse in the transparent resin. There is also a demand for additional impact strength from the cellulose structure.

[0017] In contrast, the cellulose porous structure having the specific surface area and porosity in the above ranges is easily disintegrable. Therefore, when the cellulose porous structure is kneaded into a transparent resin, the cellulose porous structure disintegrates and is dispersed in the transparent resin in a fine and nearly uniform state. Therefore, the decrease in transparency of the transparent resin is suppressed, and the inherent transparency of the transparent resin is easily maintained. On the other hand, the cellulose porous structure is dispersed finely and almost uniformly in the transparent resin, which enhances the crystallization of the transparent resin. In addition, the porous structure of the cellulose porous structure increases the number of contacts between the cellulose porous structure and the transparent resin, enhancing the modifying ability of the cellulose porous structure, which is thought to improve the impact resistance of the transparent resin.

[0018] In addition, in order to express the transparency of the transparent resin, it is preferable that the cellulose structure to be added is small in size and uniformly dispersed. For example, small-sized cellulose structures such as cellulose nanofibers are already available, but because of their high hydrogen bonding properties, they are prone to secondary aggregation when added to a transparent resin by kneading, and the size increases, which significantly reduces the transparency of the transparent resin. On the other hand, the cellulose porous structure according to this embodiment is unlikely to cause secondary aggregation in the resin by being crushed with a kneading torque, and can be uniformly dispersed in small sizes, which is thought to enable high transparency to be expressed. In addition, in terms of impact strength, it is preferable to increase the binding property (i.e., contact area) with the transparent resin in addition to uniform dispersion. Since the cellulose porous structure according to this embodiment can be dispersed in the transparent resin while being crushed by kneading as described above, the crushed surface is irregular and the contact area with the transparent resin can be increased. Therefore, high impact strength can be obtained.

[0019] From the above, it is presumed that the cellulose porous structure according to this embodiment, due to the above-mentioned configuration, can provide a resin molded article having high transparency and impact strength.

[0020] In recent years, interest in biomass resins and biodegradable resins has been growing due to environmental awareness, as represented by the SDGs (Sustainable Development Goals). In particular, among biomass resins and biodegradable resins, polylactic acid is a carbon-neutral, highly biodegradable resin, and is expected to be a substitute for petroleum-derived plastics. However, biomass resins and biodegradable resins, especially polylactic acid, have low impact resistance and are limited in their applications. If biomass resin and biodegradable resin are compounded with petroleum-based resin and modifier, the impact resistance can be improved, but this reduces the biomass content and increases the CO 2 The environmental effects such as emission reduction and petroleum resource saving are reduced. In addition, when the biomass resin and biodegradable resin are transparent resins (especially polylactic acid), the modifier impairs the inherent transparency of the resin.

[0021] However, by applying the cellulose porous structure according to this embodiment, even if a biomass resin or a biodegradable resin is used as the transparent resin, a resin molded body having a high biomass content or biodegradability, as well as high transparency and impact strength can be obtained.

[0022] For example, it has been reported that excellent moldability, strength and flexibility can be obtained by using biodegradable resin and cellulose particles with a sphericity of 0.9 or more while maintaining a high biomass content. However, because the specific surface area of ​​the cellulose particles is small, a large amount of the cellulose particles is required to achieve the desired effect, which inhibits the inherent transparency and impact resistance of the biodegradable resin. For example, it has been reported that a resin composition consisting of polylactic acid, a biodegradable polyester with a melting point of 50°C to 250°C, and a natural product has improved the biodegradation rate while maintaining the characteristics of polylactic acid (e.g., Patent Document 3). However, since the aliphatic polyester is not a biomass resin, the biomass degree is reduced. In addition, the particle size of the natural product is large, the contact area with the resin is small, and furthermore, the compatibility between polylactic acid and aliphatic polyester is low, resulting in the formation of sea-island domains, making it difficult to finely disperse, and therefore low impact resistance.

[0023] The cellulose porous structure according to this embodiment will be described in detail below.

[0024] (Cellulose and cellulose derivatives) The cellulose porous structure according to this embodiment contains at least one of cellulose and a cellulose derivative as a main component. Here, "having at least one of cellulose and a cellulose derivative as the main component" means that the total content of cellulose and the cellulose derivative in the cellulose porous structure is 90 mass% or more, preferably 95 mass% or more, 98 mass% or more, or 100 mass%.

[0025] Cellulose is a polymeric compound in which numerous β-glucose molecules are polymerized in a linear chain via glycosidic bonds. On the other hand, examples of the cellulose derivatives include cellulose acylate, cellulose ether, hydroxyalkyl cellulose, and carboxymethyl cellulose. Among these, cellulose acylate is preferred as the cellulose derivative from the viewpoint of high biodegradability.

[0026] Cellulose acylate is a cellulose derivative in which at least a part of the hydroxyl groups in cellulose is replaced by an acyl group (acylation). An acyl group is a -CO-R AC (R AC represents a hydrogen atom or a hydrocarbon group.

[0027] Cellulose acylate is, for example, a cellulose derivative represented by the following general formula (CA).

[0028] [ka]

[0029] In the general formula (CA), A 1 , A 2 and A 3 Each independently represents a hydrogen atom or an acyl group, and n represents an integer of 2 or more. 1 , n A's 2 and n A's 3 At least some of the n A's in the molecule represent acyl groups. 1 may be all the same, some may be the same, or different from each other. 2 and n A 3 may be entirely the same, partially the same, or different from each other.

[0030] A 1 , A 2 and A 3 The acyl group represented by the formula (I) may have a hydrocarbon group that is linear, branched, or cyclic, but is preferably linear or branched, and more preferably linear.

[0031] A 1 , A 2 and A 3 The acyl group represented by the formula (I) may have a hydrocarbon group which is either a saturated hydrocarbon group or an unsaturated hydrocarbon group, but is more preferably a saturated hydrocarbon group.

[0032] A 1 , A 2 and A 3 The acyl group represented by the formula (I) is preferably an acyl group having a carbon number of 1 to 6. That is, the cellulose acylate is preferably an acyl group having a carbon number of 1 to 6.

[0033] A 1 , A 2 and A 3 The acyl group represented by may be a group in which a hydrogen atom in the acyl group is substituted with a halogen atom (for example, a fluorine atom, a bromine atom, an iodine atom), an oxygen atom, a nitrogen atom or the like, but is preferably unsubstituted.

[0034] A 1 , A 2 and A 3 Examples of the acyl group represented by include a formyl group, an acetyl group, a propionyl group, a butyryl group (butanoyl group), a propenoyl group, a hexanoyl group, etc. Among these, from the viewpoint of improving the biodegradation rate of the resin particles, the acyl group is more preferably an acyl group having 2 to 4 carbon atoms, and even more preferably an acyl group having 2 or 3 carbon atoms.

[0035] Examples of the cellulose acylate include cellulose acetate (cellulose monoacetate, cellulose diacetate (DAC), cellulose triacetate), cellulose acetate propionate (CAP), and cellulose acetate butyrate (CAB).

[0036] Of the cellulose acylates, cellulose acetate is preferred from the viewpoint of high biodegradability.

[0037] From the viewpoint of biodegradability, the degree of substitution of cellulose acylate is preferably from 1.7 to 2.9, more preferably from 1.9 to 2.6, further preferably from 2.0 to 2.5, particularly preferably from 2.1 to 2.4.

[0038] The degree of substitution of cellulose acylate is an index showing the degree to which hydroxyl groups of cellulose are substituted with acyl groups. In other words, the degree of substitution is an index showing the degree of acylation of cellulose acylate. Specifically, the degree of substitution means the intramolecular average number of substitutions in which three hydroxyl groups in the D-glucopyranose unit of cellulose acylate are substituted with acyl groups. The degree of substitution is 1The ratio is calculated from the integral ratio of the peaks of hydrogen derived from cellulose and hydrogen derived from acyl groups using H-NMR (JMN-ECA / JEOL RESONANCE).

[0039] These cellulose derivatives may be used alone or in combination.

[0040] -Number average molecular weight of cellulose and cellulose derivatives- The number average molecular weight of cellulose and cellulose derivatives is preferably 5,000 or more, more preferably 10,000 or more, and even more preferably 15,000 or more. When the number average molecular weight of the cellulose and cellulose derivative is within the above range, the cellulose porous structure is prevented from being finely disintegrated before being kneaded with the resin, and as a result, secondary aggregation after disintegration is prevented, and fine, nearly uniform dispersion in the resin is easily achieved, and the transparency and impact strength of the resin molded product are easily improved. However, from the viewpoint of preventing a decrease in biodegradability, the number average molecular weight of cellulose and cellulose derivatives is preferably 50,000 or less, and more preferably 30,000 or less.

[0041] The number average molecular weight of cellulose and cellulose derivatives is measured by gel permeation chromatography (differential refractometer Optilab T-rEX / Wyatt Technology, multi-angle light scattering detector DAWN HELEOS II / Wyatt Technology, columns TSKgel α-M, α-3000 each / Tosoh) using dimethylacetamide (with 0.1 M lithium chloride added) as a solvent.

[0042] (Other ingredients) The cellulose porous structure according to this embodiment may contain other components.

[0043] (Characteristics of cellulose porous structures) -Specific surface area- The specific surface area of ​​the cellulose porous structure according to this embodiment is 1 m 2 / g or more 150m 2 / g or less, preferably 10m 2 / g or more 150m 2 / g or less, more preferably 20m 2 / g or more 100m 2 / g or less. The specific surface area of ​​the cellulose porous structure is 1m 2 When the molecular weight is 1.0 or more, the ability to modify the cellulose porous structure is sufficient, and the impact resistance is improved. The specific surface area of ​​the cellulose porous structure is 150m 2 When the cellulose porous structure has a molecular weight of 1000 to 10000 kneading time, the cellulose porous structure is prevented from being pulverized before being kneaded with the resin, and as a result, secondary aggregation after pulverization is suppressed, and a fine and nearly uniform dispersion in the resin is realized, thereby improving the transparency and impact strength of the resin molded product.

[0044] The specific surface area of ​​the cellulose porous structure is the BET specific surface area, and is a value measured by automatic measurement using a multipoint method with a specific surface area / pore distribution measuring device (BELSORP MAXII, MicrotrackBell). The measurement temperature is 77K, and nitrogen gas is used as the adsorption gas. However, before the measurement, the sample (i.e., the cellulose porous structure) is subjected to pretreatment such as vacuum drying at 100° C. for 24 hours to remove water adsorbed in the pores of the sample.

[0045] -Porosity- The porosity of the cellulose porous structure according to this embodiment is 10% or more and 50% or less, preferably 15% or more and 50% or less, and more preferably 20% or more and 50% or less. When the porosity of the cellulose porous structure is 10% or more, the modifying ability of the cellulose porous structure becomes sufficient, and the impact resistance is improved. When the porosity of the cellulose porous structure is 50% or less, the cellulose porous structure is prevented from being pulverized before being kneaded with the resin, which results in suppressing secondary aggregation after pulverization, realizing fine and nearly uniform dispersion in the resin, and improving the transparency and impact strength of the resin molded product.

[0046] The porosity of the cellulose porous structure is measured as follows. The cellulose porous structure is observed at a magnification of 25,000 times using a scanning electron microscope (SEM) to obtain an SEM image. The SEM image is imported into the image processing software "ImageJ" and binarized to determine the area of ​​the entire cellulose porous structure and the area of ​​the pores. The ratio of the pores in the cellulose porous structure to the area of ​​the entire cellulose porous structure is then calculated to determine the porosity of the cellulose porous structure. This operation is carried out 10 times and the average value is calculated.

[0047] -Average diameter- The average diameter of the cellulose porous structure is preferably from 1 μm to 500 μm, more preferably from 1 μm to 355 μm, and even more preferably from 1 μm to 150 μm. When the average diameter of the cellulose porous structure is 1 μm or more, when the cellulose porous structure is kneaded with a resin, the cellulose porous structure collapses, making it easier to achieve fine, nearly uniform dispersion in the resin, and improving the transparency and impact strength of the resin molded product. When the average diameter of the cellulose porous structure is 500 μm or less, the cellulose porous structure is prevented from being pulverized before being kneaded with the resin, which results in suppressing secondary aggregation after pulverization, making it easier to achieve fine and nearly uniform dispersion in the resin, and improving the transparency and impact strength of the resin molded product.

[0048] The average diameter of the cellulose porous structure was measured as follows. The cellulose porous structure is observed at a magnification of 250 times using a scanning electron microscope (SEM) to obtain a threshold SEM image. The SEM image is imported into the image processing software "ImageJ" and the circle equivalent diameter is calculated from the area of ​​the cellulose porous structure. The average circle equivalent diameter of 20 cellulose porous structures is then calculated and used as the average diameter.

[0049] -Average diameter of cellulose porous structures in resin- In the cellulose porous structure of this embodiment, when the cellulose porous structure is kneaded with a resin, the cellulose porous structure is present in the resin preferably with an average diameter of 50 μm or less, more preferably with an average diameter of 10 μm or less, and even more preferably with an average diameter of 1 μm or less. When the cellulose porous structure is present in the resin with an average diameter of 50 μm or less, it is finely dispersed in the resin, and the transparency and impact strength of the resin molding are improved. In addition, from the viewpoint of fully utilizing the modifying ability of the cellulose resin and improving the impact resistance of the resin molded body, when the cellulose porous structure is kneaded with the resin, it is preferable that the cellulose porous structure is present in the resin with an average diameter of 0.05 μm or more.

[0050] The average diameter of the cellulose porous structure in the resin is the average diameter of the cellulose porous structure when the cellulose porous structure is kneaded with the resin under the conditions in the later-described "Example 1." The average diameter of the cellulose porous structure is measured as follows. A resin composition in which a cellulose porous structure is kneaded with a resin is cut. The cellulose porous structure of the cut surface of the resin composition is observed at a magnification of 1000 times using a scanning electron microscope (SEM) to obtain an SEM image. The SEM image is imported into the image processing software "ImageJ" and the circle equivalent diameter is calculated from the area of ​​the cellulose porous structure. The average circle equivalent diameter of the 20 cellulose porous structures is then calculated and used as the average diameter.

[0051] -specific gravity- The specific gravity of the cellulose porous structure according to this embodiment is 0.5 g / cm 3 More than 1.15g / cm 3 Less than 0.60 g / cm is preferred. 3 More than 1.0g / cm 3 Less than 0.70 g / cm is more preferable. 3 More than 0.90g / cm 3 The following is even more preferred: When the specific gravity of the cellulose porous structure is within the above range, when the cellulose porous structure is kneaded into a resin, it becomes easier to achieve a fine, nearly uniform dispersion in the resin, and the transparency and impact strength of the resin molded product are improved.

[0052] The specific gravity of the cellulose porous structure was measured as follows. A 30 g sample of the structure was measured three times by the immersion method using an automatic specific gravity meter (DSG-1, manufactured by Toyo Seiki Seisakusho Co., Ltd.), except that the measurement liquid was changed from water to ethanol, and the average was taken as the measured value.

[0053] (Method of manufacturing a cellulose porous structure) The cellulose porous structure according to this embodiment can be obtained, for example, by the following method. (1) A cellulose derivative is added to a good solvent for the cellulose derivative, and then heated to obtain a solution A in which the cellulose derivative is dissolved in the good solvent. (2) A poor solvent for the cellulose derivative is added to solution A to obtain solution B. (3) Solution B is rapidly cooled, and a gel-like substance of the cellulose derivative is produced by phase separation. (4) After the gel-like substance is washed, it is dried to obtain a cellulose porous structure mainly composed of a cellulose derivative. (5) The obtained cellulose porous structure may be crushed and sieved to remove coarse particles and aggregates, if necessary. The crushing method is not particularly limited, but may be performed using a dry grinding device such as a jet mill, a vibration mill, a ball mill, or a pin mill. The sieving method may be performed using a known device such as a vibration sieve or an air sieving machine.

[0054] Here, by saponifying the gel-like substance (i.e., by saponifying the cellulose derivative), a cellulose porous structure mainly composed of cellulose or a cellulose derivative mainly composed of cellulose and a cellulose derivative is obtained, depending on the degree of saponification.

[0055] <Resin composition> The resin composition according to this embodiment is a resin composition made of a kneaded product containing a transparent resin and the cellulose porous structure according to this embodiment. Specifically, the resin composition according to the present embodiment contains a transparent resin and a disintegrated product of the cellulose porous structure according to the present embodiment that is disintegrated by kneading with the transparent resin.

[0056] (transparent resin) The transparent resin is a resin that has a haze value of 15% or less when the thickness of a molded article made of the transparent resin alone is 2 mm.

[0057] Examples of transparent resins include vinyl resins and amorphous polyolefins, which are homopolymers of monomers such as styrenes (e.g., styrene, parachlorostyrene, α-methylstyrene, etc.), (meth)acrylic acid esters (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), olefins (e.g., ethylene, propylene, butadiene, etc.), and vinyl alcohol, or copolymers of two or more of these monomers. Examples of the transparent resin include non-vinyl resins such as polyester resins, epoxy resins, polyurethane resins, polyamide resins, polyether resins, and modified rosin, mixtures of these with the above-mentioned vinyl resins, and graft polymers obtained by polymerizing vinyl monomers in the coexistence of these. The transparent resin also includes natural polymers.

[0058] Examples of the polyester resin include an aliphatic polyester resin and an aliphatic aromatic polyester resin. Examples of aliphatic polyester resins include polyhydroxyalkanoates such as polylactic acid (PLA), polyglycolic acid (PGA), polyhydroxyalkanoates (PHA), polycaprolactone, polybutylene succinate (PBS), polybutylene succinate / adipate (PBSA), and polyethylene succinate (PBA). Examples of the aliphatic aromatic polyester resin include polybutylene adipate / terephthalate copolymer resin (PBAT), polytetramethylene adipate / terephthalate copolymer resin, and the like.

[0059] Examples of natural polymers include starch, cellulose, chitin, chitosan, gluten, gelatin, zein, soy protein, collagen, and keratin.

[0060] The biodegradable resin also includes cellulose derivatives (cellulose acylate, cellulose ether, hydroxyalkyl cellulose, carboxymethyl cellulose).

[0061] Among these transparent resins, from the viewpoint of environmental compatibility, biomass resins and biodegradable resins are preferred as transparent resins, and resins that fall into both the biomass resin and biodegradable resin categories (particularly polylactic acid) are preferred. The biodegradable resin is a resin that is decomposed by microorganisms into water and carbon dioxide, and is a resin other than cellulose. Specifically, in this embodiment, the biodegradable resin means a resin whose aerobic biodegradability measured according to a method conforming to ISO 14855-1:2012 is 5% or more in 28 days.

[0062] These transparent resins may be used alone or in combination of two or more kinds.

[0063] The content of the transparent resin in the resin composition is preferably 90% by mass or more and 99.9% by mass or less, and more preferably 95% by mass or more and 99.9% by mass or less.

[0064] (Content of cellulose porous structure) The content of the cellulose porous structure is preferably from 0.1% by mass to 20% by mass, more preferably from 1% by mass to 10% by mass, and further preferably from 1% by mass to 5% by mass, based on the transparent resin. When the content of the cellulose porous structure is within the above range, a resin molded product having sufficiently high transparency and impact resistance can be easily obtained.

[0065] (Other ingredients) The resin composition according to the present embodiment may contain other components. Examples of other components include plasticizers, flame retardants, compatibilizers, release agents, light resistance agents, weather resistance agents, colorants, pigments, modifiers, anti-drip agents, antistatic agents, hydrolysis inhibitors, fillers, reinforcing agents (glass fibers, carbon fibers, talc, clay, mica, glass flakes, milled glass, glass beads, crystalline silica, alumina, silicon nitride, aluminum nitride, boron nitride, etc.), acid acceptors (oxides such as magnesium oxide and aluminum oxide; metal hydroxides such as magnesium hydroxide, calcium hydroxide, aluminum hydroxide, and hydrotalcite; calcium carbonate; talc; etc.), and reactive trapping agents (for example, epoxy compounds, acid anhydride compounds, carbodiimides, etc.). The content of each of the other components is preferably 0% by mass or more and 5% by mass or less based on the total amount of the resin composition, where "0% by mass" means that no other components are included.

[0066] (Characteristics of resin composition) -Average diameter of cellulose porous structures in transparent resin- In the resin composition according to this embodiment, the cellulose porous structure (i.e., the collapsed product of the cellulose porous structure according to the above embodiment) is present in the transparent resin preferably with an average diameter of 50 μm or less, more preferably with an average diameter of 10 μm or less, and even more preferably with an average diameter of 1 μm or less. When the cellulose porous structure is present in a transparent resin with an average diameter of 50 μm or less, it is finely dispersed in the resin, improving the transparency and impact strength of the resin composition.

[0067] The average diameter of the cellulose porous structure in the transparent resin is measured as follows. The resin composition is cut. The cellulose porous structure of the cut surface of the resin composition is observed at 1000 times magnification using a scanning electron microscope (SEM) to obtain an SEM image. The SEM image is imported into the image processing software "ImageJ" and the circle equivalent diameter is calculated from the area of ​​the cellulose porous structure. Then, the average circle equivalent diameter of 20 cellulose porous structures is calculated and used as the average diameter.

[0068] -Haze value- In the resin composition according to the present embodiment, the haze value when the thickness of the molded article of the resin composition is 2 mm is preferably 15% or less, more preferably 10% or less, and even more preferably 7% or less. The haze value is ideally 0%. When the haze value is within the above range, a resin molded article having sufficiently high transparency can be obtained.

[0069] (Charpy impact strength) The Charpy impact strength of the resin composition according to this embodiment is 1 kJ / m 2 More than 2 kJ / m is preferable. 2 More preferably, 2.5 kJ / m or more. 2 More preferably, 3 kJ / m 2 More than 4 kJ / m is particularly preferred. 2 The above is most preferable. When the Charpy impact strength is within the above range, a resin molding having sufficiently high impact resistance can be easily obtained.

[0070] The haze value and Charpy impact strength herein are values ​​measured by the method described in the "Examples" section below.

[0071] (Method of producing resin composition) Examples of the method for producing the resin composition according to the present embodiment include a method of mixing the components and melt-kneading them. The melt-kneading means is not particularly limited, and examples thereof include a twin-screw extruder, a Henschel mixer, a Banbury mixer, a single-screw extruder, a multi-screw extruder, and a co-kneader. By controlling the kneading conditions, a resin composition containing a transparent resin and a collapsed product of the cellulose porous structure according to this embodiment collapsed by kneading the transparent resin can be obtained.

[0072] <Resin molded body> The resin molded article according to the present embodiment includes the resin composition according to the present embodiment, that is, the resin molded article according to the present embodiment has the same composition as the resin composition according to the present embodiment.

[0073] As a molding method for the resin molded article according to this embodiment, an injection molded article obtained by injection molding can be mentioned from the viewpoint of a high degree of freedom in shape. Injection molding of the resin molded body according to this embodiment may be performed using commercially available equipment such as Nissei Plastic Industrial Co., Ltd.'s NEX500, Nissei Plastic Industrial Co., Ltd.'s NEX150, Nissei Plastic Industrial Co., Ltd.'s NEX7000, Nissei Plastic Industrial Co., Ltd.'s PNX40, or Sumitomo Machinery Co., Ltd.'s SE50D.

[0074] The resin molded article according to the present embodiment may be a resin molded article obtained by other molding methods, such as extrusion molding, blow molding, heat press molding, calendar molding, coating molding, cast molding, dipping molding, vacuum molding, and transfer molding.

[0075] Applications of the resin molded article according to this embodiment include housings for electronic or electrical devices or home appliances; various parts for electronic or electrical devices or home appliances; interior parts for automobiles; building block toys; plastic model kits; storage cases for CD-ROMs or DVDs; tableware; beverage bottles; food trays; wrapping materials; films; sheets; and the like. EXAMPLES

[0076] Examples will be described below, but the present invention is not limited to these examples. In the following description, unless otherwise specified, all "parts" and "%" are based on mass.

[0077] <Preparation of cellulose porous structure> (Cellulose porous structure CPS (1)) In a container, 5 parts by mass of cellulose acetate DAC(1) was added to 20 parts by mass of dimethylformamide, and the resulting solution A was stirred at 90°C for 1 hour. After dissolving cellulose acetate in dimethylformamide in solution A, 25 parts by mass of hexanol was slowly added to solution A while stirring, and the resulting solution B was stirred for 1 hour. Then, solution B was immersed in ice water together with the container to rapidly cool, and a gel product of a cellulose porous structure was obtained by phase separation. The resulting gel product was washed with 200 parts by mass of ethanol and vacuum dried at 50°C for 24 hours to obtain a cellulose porous structure. The structure was then crushed in a mill mixer and sieved through a 106 μm sieve to obtain a finely pulverized cellulose structure.

[0078] (Cellulose Porous Structure CPS (2)) A cellulose porous structure CPS (2) was obtained in the same manner as the cellulose porous structure CPS (1), except that the mesh size of the sieve was 53 μm.

[0079] (Cellulose Porous Structure CPS (3)) A cellulose porous structure CPS (3) was obtained in the same manner as the cellulose porous structure CPS (1) except that the amount of cellulose acetate DAC (1) was 7.5 parts by mass.

[0080] (Cellulose Porous Structure CPS (4)) A cellulose porous structure CPS (4) was obtained in the same manner as the cellulose porous structure CPS (1) except that the amount of cellulose acetate DAC (1) was 3.5 parts by mass.

[0081] (Cellulose Porous Structure CPS (5)) A cellulose porous structure CPS (5) was obtained in the same manner as for the cellulose porous structure CPS (1), except that the cellulose acetate DAC (1) was changed to DAC (2).

[0082] (Cellulose Porous Structure CPS (6)) A cellulose porous structure CPS (6) was obtained in the same manner as for the cellulose porous structure CPS (1), except that the cellulose acetate DAC (1) was changed to DAC (3).

[0083] (Cellulose porous structure CPS (7)) A cellulose porous structure CPS(2) was obtained in the same manner as for the cellulose porous structure CPS(1), except that the cellulose acetate DAC(1) was changed to DAC(4).

[0084] (Cellulose porous structure CPS (8)) A cellulose porous structure CPS (8) was obtained in the same manner as the cellulose porous structure CPS (1), except that cellulose acetate was changed to triacetyl cellulose.

[0085] (Cellulose Porous Structure CPS (9)) A cellulose porous structure CPS (9) was obtained in the same manner as the cellulose porous structure CPS (1), except that cellulose acetate was changed to cellulose acetate propionate.

[0086] (Cellulose Porous Structure CPS (10)) A cellulose porous structure CPS (10) was obtained in the same manner as the cellulose porous structure CPS (1), except that cellulose acetate was changed to cellulose acetate butyrate.

[0087] (Cellulose Porous Structure CPS (11)) A cellulose porous structure CPS (11) was obtained in the same manner as in the cellulose porous structure CPS (1), except that the gel product was subjected to alkaline saponification before being washed with ethanol.

[0088] (Cellulose porous structure CPS (12)) A cellulose porous structure CPS (12) was obtained in the same manner as the cellulose porous structure CPS (1), except that the mesh size of the sieve was set to 500 μm.

[0089] (Cellulose Porous Structure CPS (13)) A cellulose porous structure CPS (13) was obtained in the same manner as the cellulose porous structure CPS (1), except that the amount of cellulose acetate was 12.5 parts by mass.

[0090] (Cellulose Porous Structure CPS (14)) A cellulose porous structure CPS (14) was obtained in the same manner as for the cellulose porous structure CPS (1), except that the cellulose acetate DAC (1) was changed to DAC (5).

[0091] (Cellulose Porous Structure CPS (15)) A cellulose porous structure CPS (15) was obtained in the same manner as the cellulose porous structure CPS (1), except that the sieving step was not performed.

[0092] (Cellulose Porous Structure CPS (16)) A cellulose structure CS(16) was obtained in the same manner as for the cellulose structure CS(1), except that the amount of dimethylformamide was changed to 180 parts by mass and the amount of hexanol was changed to 450 parts by mass.

[0093] (Cellulose Porous Structure CPS (17)) A cellulose porous structure CPS (17) was obtained in the same manner as the cellulose porous structure CPS (1) except that the amount of cellulose acetate was 15 parts by mass.

[0094] (Cellulose porous structure CPS (18)) A cellulose porous structure CPS (18) was obtained in the same manner as for the cellulose porous structure CPS (1), except that the amount of dimethylformamide was changed to 180 parts by mass and the amount of hexanol was changed to 450 parts by mass.

[0095] (Cellulose porous structure CPS (C1)) Cellulose acetate DAC (1) was crushed in a mill mixer and then sieved through a 106 μm sieve to obtain a cellulose structure (C1).

[0096] (Cellulose porous structure CPS (C2)) 130 parts by mass of cellulose acetate DAC(1) was dissolved in 870 parts by mass of ethyl acetate. This was added to a dispersion of 50 parts by mass of calcium carbonate dispersed in 500 parts by mass of pure water, and stirred for 3 hours. This was added to a dispersion of 4 parts by mass of carboxymethylcellulose and 200 parts by mass of methyl ethyl ketone dispersed in 600 parts by mass of pure water, and stirred for 5 minutes with a high-speed emulsifier. 10 g of sodium hydroxide was added to this, and the mixture was stirred at 80°C for 3 hours to remove ethyl acetate and methyl ethyl ketone. 10 g of dilute hydrochloric acid was added to this, and the residue was filtered to obtain nonporous cellulose particles.

[0097] (Characteristics of cellulose porous structures) The following properties of the obtained cellulose porous structure were measured according to the above-mentioned methods: Average diameter of the cellulose porous structure - Specific surface area of ​​cellulose porous structure (indicated as "BET" in the table) Porosity of cellulose porous structures - Specific gravity of cellulose porous structure When the cellulose porous structure was kneaded with the resin under the same transparent resin and kneading conditions as in Example 1, the average diameter of the cellulose porous structure present in the resin (referred to as "dispersed diameter" in the table)

[0098] <Examples 1 to 20 and Comparative Examples 1 to 6> Each component was charged into a twin-screw extruder (Shibaura Machine Co., Ltd., TEM58SS) under the conditions of composition, cylinder temperature, and kneading torque shown in Table 1, and each component was kneaded, cooled, and cut to obtain resin pellets (corresponding to the resin composition).

[0099] <Evaluation> (Resin molding) Under the conditions of cylinder temperature, mold temperature, and mold retention time shown in Table 1, the resin pellets of each example were loaded into an injection molding machine (Nissei Plastic Industrial Co., Ltd., NEX500) and molded into ISO multipurpose dumbbell test pieces (test section width 8 mm × thickness 4 mm × length 110 mm).

[0100] (Haze value) The haze value of the test portion of the obtained ISO multipurpose dumbbell test piece was measured using a haze meter (TZ7700, manufactured by Nippon Denshoku Industries Co., Ltd.).

[0101] (Charpy impact strength) The obtained ISO multipurpose dumbbell test pieces were A-notched according to the method of ISO179-1:2010. Then, the Charpy impact strength of the processed test pieces was measured at room temperature (25° C.) using an impact strength measuring device (Charpy Auto Impact Tester, manufactured by Toyo Seiki Seisakusho).

[0102] <Materials used> The materials used will be described in detail below. -Raw materials for additives- DAC(1): Eastman Chemical Co., Ltd. "Product name CA398-3", cellulose diacetate, number average molecular weight Mn=15000 DAC(2): Daicel Corporation, "Product name L20", cellulose diacetate, number average molecular weight Mn=15000 DAC(3): Daicel Corporation, "Product name L50", cellulose diacetate, number average molecular weight Mn=50,000 DAC(4): Daicel Corporation, "Product name L70", cellulose diacetate, number average molecular weight Mn=75,000 ·DAC(5): In-house synthesized cellulose diacetate, number average molecular weight Mn=13000 TAC: Daicel Corporation, product name LT-35, cellulose triacetate, number average molecular weight Mn=50,000 CAP: Eastman Chemical Co., Ltd. "Product name CAP482-20", cellulose acetate propionate, number average molecular weight Mn = 72,000 CAB: Eastman Chemical Co., Ltd. "Product name CAB381-20", cellulose acetate butyrate, number average molecular weight Mn = 85,000 CNF "Manufacturer: Sugino Machine Co., Ltd. "Product name: BiNFIS DRY", Cellulose nanofiber

[0103] -Transparent resin- PMMA: Polymethyl methacrylate (Asahi Kasei Chemical, Delpet 720V) PET: Polyethylene terephthalate (Lotte Chemical, BCB80) PP: Polypropylene (Japan Polypropylene, Novatec PP MG03BD) PS: Polystyrene (PS Japan, GPPS-HF77)

[0104] [Table 1-1]

[0105] [Table 1-2]

[0106] From the above results, it is understood that in this example, a resin molded product (that is, a resin composition) having higher transparency and impact strength than the comparative example can be obtained.

[0107] The present embodiment includes the following aspects. (((1))) Contains at least one of cellulose and a cellulose derivative as a main component, Specific surface area is 1m 2 / g or more 150m 2 / g or less, A cellulose porous structure having a porosity of 10% or more and 50% or less. (((2))) The cellulose porous structure according to (((1))), wherein when the cellulose porous structure is kneaded with a resin, the cellulose porous structure is present in the resin with an average diameter of 50 μm or less. (((3))) The cellulose porous structure according to ((1))) or (((2))), wherein the cellulose and the cellulose derivative have a number average molecular weight of 15,000 or more. (((4))) The cellulose porous structure according to any one of ((1))) to (((3))), wherein the cellulose derivative is cellulose acetate. (((5))) Transparent resin, A cellulose porous structure according to any one of (((1))) to (((4))), A resin composition comprising a kneaded product containing the above. (((6))) The resin composition according to (((5))), wherein the haze value of a molded article of the resin composition is 15% or less when the thickness of the molded article is 2 mm. (((7))) Charpy impact strength is 2.5kJ / m 2 The resin composition according to (((5))) or (((6))).

[0108] The advantages of the above aspect are as follows. According to the invention of (((1))), a cellulose porous structure containing at least one of cellulose and a cellulose derivative as a main component has a specific surface area of ​​1 m 2 / g or less than 150m 2 / g or more, or a porosity of less than 10% or more than 50%, a resin molded article having high transparency and impact strength can be obtained.

[0109] According to the invention related to (((2))), there is provided a cellulose porous structure which, when kneaded with a resin, gives a resin molded product having higher transparency and impact strength than when the cellulose porous structure is present in the resin with an average diameter of more than 50 μm. According to the invention related to (((3))), a cellulose porous structure is provided which can give a resin molded article having higher transparency and impact strength than when the number average molecular weight of cellulose and cellulose derivatives is less than 15,000. According to the invention related to (((4))), there is provided a cellulose porous structure which can give a resin molded article which is not only biodegradable but also has high transparency and impact strength, as compared with the case where the cellulose derivative is cellulose acetate propionate.

[0110] According to the invention of (((5))), (((6))) or (((7))), a cellulose porous structure containing at least one of cellulose and a cellulose derivative as a main component has a specific surface area of ​​1 m 2 / g or less than 150m 2 The resin composition provides a resin molded product having higher transparency and impact strength than when a cellulose porous structure having a viscosity of more than 100 μm / g or a porosity of less than 10% or more than 50% is used.

Claims

1. Contains at least one of cellulose and a cellulose derivative as a main component, Specific surface area is 1m 2 / g or more 150m 2 / g or less, A cellulose porous structure having a porosity of 10% or more and 50% or less.

2. The cellulose porous structure according to claim 1 , wherein when the cellulose porous structure is kneaded with a resin, the cellulose porous structure is present in the resin with an average diameter of 50 μm or less.

3. The cellulose porous structure according to claim 1 , wherein the cellulose and the cellulose derivative have a number average molecular weight of 15,000 or more.

4. 2. The cellulose porous structure according to claim 1, wherein the cellulose derivative is cellulose acetate.

5. Transparent resin, The cellulose porous structure according to any one of claims 1 to 4, A resin composition comprising a kneaded product containing the above.

6. The resin composition according to claim 5, wherein the haze value of a molded article of the resin composition is 15% or less when the thickness of the molded article is 2 mm.

7. Charpy impact strength is 2.5 kJ / m 2 The resin composition according to claim 5 .

Citation Information

Patent Citations

  • Polylactate resin composition

    JP1999241009A

  • Method for producing porous cellulose medium

    WO2016159334A1

  • Cellulose acetate-containing particles, cosmetic composition, and method for producing cellulose acetate-containing particles

    WO2020188698A1